Building sample in regular quantitative public opinion research (omnibus poll) in Russian Public Opinion Research Center and Levada Center (The Journal of Psychology and Sociology, 2016)
The article deals with the method of sampling in quantitative studies of public opinion (omnibus surveys) carried out in two competent Russian organizations – the Russian Public Opinion Research Center and the Levada Center. Omnibus surveys have a special place in the activities of the two organizations and have long been playing a prominent public role. Authors study the volume and type of sample. The attention is focused on the main features of probability sampling, which is used in institutions (and, namely, stratified multistage probability sample). Ensuring the prob ability that each element of the population in the spot and the possibility of calculat ing this probability are the main principles and advantages, thanks to which in the omnibus surveys used a probabilistic sampling method. Procedure of constructing the sample in two organizations is analyzed, compared and expressed in table. The technique does not seem difficult, people can understand and evaluate the degree of commitment to ensure representativeness.Also is considered the boundaries of public opinion. Public opinion is not a good means of philosophical research, may assign to the professional competence, include more social flaws as ethnocentrism then humanistic ideals, it is subject to manipulation. Also, based on the logic of some world religions, public opinion can not establish what is good or evil. Despite the limitations, the public opinion studies are useful, especially as a democratic tool in the control of the authorities. After understanding boundaries, social scientists should focus on ensuring the reliability.